2010
DOI: 10.1002/j.2333-8504.2010.tb02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Generating Automated Text Complexity Classifications That Are Aligned With Targeted Text Complexity Standards

Abstract: The Common Core Standards call for students to be exposed to a much greater level of text complexity than has been the norm in schools for the past forty years. Textbook publishers, teachers, and assessment developers are being asked to refocus materials and methods to ensure that students are challenged to read texts at steadily increasing complexity levels as they progress through school so that all students remain on track to achieve college and career readiness by the end of 12th grade. Although automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 30 publications
(33 reference statements)
1
47
0
5
Order By: Relevance
“…The dimensions obtained in the most recent factor analysis in this line of research (Sheehan et al, 2010) involve the features and dimensions shown in Table 1.…”
Section: Modeling Writing Development and Writing Constructs: An Apprmentioning
confidence: 99%
“…The dimensions obtained in the most recent factor analysis in this line of research (Sheehan et al, 2010) involve the features and dimensions shown in Table 1.…”
Section: Modeling Writing Development and Writing Constructs: An Apprmentioning
confidence: 99%
“…Because many important complexity features are known to function differently within texts from different genres (Hiebert, 2012;Hiebert & Mesmer, 2013a, 2013bSheehan, 2013;Sheehan, Flor, & Napolitano, 2013;Sheehan, Kostin, Futagi, & Flor, 2010), three distinct prediction models are estimated: one optimized for application to informational texts, one optimized for application to literary texts, and one optimized for application to mixed texts (i.e., texts that incorporate a mixture of informational and literary elements). 2 Additional information about each step is summarized below.…”
Section: An Overview Of the Approachmentioning
confidence: 99%
“…Methods for addressing this problem are discussed in a number of recent papers (see e.g., Deane, Sheehan, Sabatini, Futagi, & Kostin, 2006;Graesser, McNamara, & Kulikowich, 2011;Sheehan, Kostin, & Futagi, 2007;Sheehan et al, 2010). In each case, a two-step solution is proposed.…”
Section: Step 2: Define Construct-relevant Text Featuresmentioning
confidence: 99%
“…These texts serve as exemplars for the level of reading ability at a given grade level. This corpus was introduced as an evaluation corpus for readability models in the recent past (Sheehan et al, 2010;Nelson et al, 2012;Flor et al, 2013), so we used it to compare our model with other systems.…”
Section: Corporamentioning
confidence: 99%